Stimulating effect of a low-molecular fraction (below 5 kDa) from cord blood on glycogenolysis in neutrophils of human donor blood leukoconcentrate - Gulevskyy, O.K.; Gulevskyy, O.K.; Akhatova, Yu. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
A semiquantitative evaluation of the glycogen content in neutrophils of freshly isolated and cryopreserved leukoconcentrates subjected to the incubation in a medium containing a low-molecular fraction (below 5 kD) from cord blood (0.15 mg/ml) is performed. It is found that the fraction contributed to glycogenolysis in cryopreserved neutrophils, which is manifested as a significant reduction in the mean cytochemical coefficient. It is shown that the effect of the low-molecular fraction from cord blood on glycogenolysis is blocked by a glycolysis inhibitor, sodium iodoacetate. The obtained data reveal a mechanism of the stimulating effect of the low-molecular fraction from cord blood on the energy metabolism of leukoconcentrate cells.